Knowledge of the vaccinators: operational aspects in the administration of the vaccine - Maria de Lourdes Coelho Pinto; Joselany Áfio Caetano; Enedina Soares (Rev Rene)
Exploratory, descriptive study in order to identify the knowledge of vaccinators, concerning operational aspects, on vaccine administration. Data were collected from a group of vaccinators from the immunization program in a city of Ceará, from July/1998 through March/1999. The sample involved 30 vaccinators. Results showed that vaccinators have little knowledge on the theoretical and operational aspects of the vaccine such technical ability of the vaccinators at the moment of dilution and preparation of the vaccines, lack of confidence and of basic cares before, during and after application of the immunobiologicals, there were verified flaus concerning conservation and discard of the vaccines, there is either no orientation or wrong orientation when provided by vaccinators.